Effect of Long-Term 3D Spheroid Culture on WJ-MSC - Agnieszka Kaminska; Aleksandra Wedzinska; Marta Kot; Anna Sarnowska (Cells, 2021)
The aim of our work was to develop a protocol enabling a derivation of mesenchymal stem/stromal cell (MSC) subpopulation with increased expression of pluripotent and neural genes. For this purpose we used a 3D spheroid culture system optimal for neural stem cells propagation. Although 2D culture conditions are typical and characteristic for MSC, under special treatment these cells can be cultured for a short time in 3D conditions. We examined the effects of prolonged 3D spheroid culture on MSC in hope to select cells with primitive features. Wharton Jelly derived MSC (WJ-MSC) were cultured in 3D neurosphere induction medium for about 20 days in vitro. Then, cells were transported to 2D conditions and confront to the initial population and population constantly cultured in 2D. 3D spheroids culture of WJ-MSC resulted in increased senescence, decreased stemness and proliferation. However long-termed 3D spheroid culture allowed for selection of cells exhibiting increased expression of early neural and SSEA4 markers what might indicate the survival of cell subpopulation with unique features.